(untitled) (Journal of Economic Research & Business Administration, 2015)
This paper has examined the development of investment processes in the regions of the Republic of Kazakhstan, on the example of the West Kazakhstan, in the particular Atyrau and Mangistau regions and their impact on their social development.We have identified qualitative and quantitative social effects of foreign direct investment in Western Kazakhstan. To identify and analyze the socio-economic impact of investments, we haveestimated the correlation coefficients, on the basis which, we have defined the relationship between statistics and interdependence of economic and social indicators characterizing the level of socio- economic development of regions of Western Kazakhstan. We also have considered the influence of foreign direct investment on socio-economic indicators. The social effect under consideration enhances economic cost effectiveness of investment projects. Thus, the social and economic effects are not only interrelated, but also interdependent.